Public health and river ecosystems: a study of the relationship between the dynamics of the Paraná River and piranha attacks (SigMe, 2025)
Palometa attacks on humans in the Paraná River floodplain, although infrequent, represent a significant risk in contexts of high tourist pressure and hydrological alterations. This study integrated ecological, environmental, and clinical data to understand the factors influencing the occurrence of these events. The spatial analysis of georeferenced records revealed a concentration of attacks in lentic or low-flow environments, especially in Santa Fe, Rosario, and Garupá, and an association with specific environmental conditions: high temperatures (30–32 °C) and summer low water levels. The species involved —Serrasalmus marginatus, S. maculatus, and Pygocentrus nattereri—show different ecological patterns, with S. marginatus being the most frequently recorded in incidents, exhibiting high aggression and territorial behavior during the reproductive period. Most attacks are concentrated on the lower limbs and usually occur in reduced sections of the river where human activity coincides with the concentration of fish, especially during the summer. A correlation is highlighted between the increase in water temperature and the intensification of the metabolism and aggressiveness of these fish, which increases the probability of interaction with bathers. This seasonal pattern reinforces the need for a preventive approach that includes environmental monitoring, educational campaigns, and medical protocols for injury care. Overall, the results provide a scientific basis for developing risk management strategies in recreational areas, integrating ecological and social variables in a context of regional environmental change
Keywords: Human-icthyofauna interactions; Biting events; Recreational areas; Floodplain; Hydroclimatic variation